Pembinaan Toleransi dan Penanaman Nilai-Nilai Pendidikan Islam dalam Pembentukan Karakter Islami Anak Usia Dini - Ida Windi Wahyuni (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2022)
The goal of this study is to discuss how to encourage tolerance and implant Islamic principles in the development of Islamic character. The goal of this essay is to give parents, educators, and community leaders an overview of the necessity of cultivating tolerance and instilling Islamic educational ideals in the formation of Islamic character in order to establish religious peace in the community. A literature review was used to perform this investigation. The data for this study was compiled from various collections of scientific publications as the primary source, which was then examined and assessed to synthesize and draw conclusions from the numerous materials obtained. Early childhood is an ideal period to begin the formation of Islamic character, with parents and teachers playing an important part in this process by teaching children to apply Islamic character principles and monitoring their growth. The aqidah method, worship approach, and moral education approach are used to develop tolerance and instill Islamic educational ideals in the formation of Islamic character in early infancy, according to the study's findings. The exemplary technique, the habit method, the counsel method, the attention method, the reward and punishment approach, the repetition method, and the active involvement method are all ways that can be used. In addition, there are supporting elements such as educational background, finances, communication, modeling, and orange cooperation with instructors. Social media, electronics, living environment, and peer contact are all inhibiting factors.